Home page for accesible maths 6 Chapter 6 contents

Style control - access keys in brackets

Font (2 3) - + Letter spacing (4 5) - + Word spacing (6 7) - + Line spacing (8 9) - +

6.48 Example

Example.

Find the inverse Laplace transform of 5(s+1)(s2+4)\frac{5}{(s+1)(s^{2}+4)}.

We use partial fractions: we have to find A,B,CA,B,C such that 5(s+1)(s2+4)=As+1+Bs+Cs2+4.\frac{5}{(s+1)(s^{2}+4)}={\frac{A}{s+1}+\frac{Bs+C}{s^{2}+4}.} Multiplying through, we obtain

5=A(s2+4)+(Bs+C)(s+1)=(A+B)s2+(B+C)s+4A+C.5={A(s^{2}+4)+(Bs+C)(s+1)=}\,{(A+B)s^{2}+(B+C)s+4A+C.}

From the first two terms we obtain: A=-B{A=-B} and B=-C,{B=-C,} so that A=CA=C. Then the constant term 4A+C=5A=5{4A+C=5A}=5, so that A=1.A={1.} Thus we want to find the inverse Laplace transform of 1s+1+1-ss2+4\frac{1}{s+1}+\frac{1-s}{s^{2}+4}. By Theorem 6.47 and the table on slide 6.44, the answer is: e-x+12sin2x-cos2xe^{-x}+\frac{1}{2}\sin 2x-\cos 2x.